The Influence of Asam Sunti Instant Seasoning on the Sensory Attributes of Fried Rice - Laili Suhairi; Tazkiatun Nufus; Zuraini Mahyiddin; Yuli Heirina Hamid; Indani (Jurnal Penelitian Pendidikan IPA, 2025)
Asam sunti is a traditional Acehnese seasoning made from dried bilimbi fruit (Averrhoa bilimbi L.). This study aims to examine the organoleptic characteristics, standard recipe, consumer acceptance, and shelf life of instant fried rice seasoning with the addition of asam sunti. A quantitative approach was employed using an experimental method. Data were collected through observation tests by five expert panelists (Culinary Arts Lecturers, Family Welfare Education Department, FKIP, Syiah Kuala University) and an acceptance test by 30 general consumer panelists. The results showed that the third treatment (BA3) had the best organoleptic characteristics in terms of color, aroma, texture, and taste, according to both expert and consumer panelists. The BA3 fried rice had a mocha-brown color, a spiced aroma, a savory taste, and a dry texture. The research hypothesis was accepted, as the addition of asam sunti had a significant effect on the organoleptic characteristics and consumer acceptance. Both expert sources and consumers favored the BA3 treatment because it provided a unique and appetizing traditional flavor. In conclusion, the asam sunti instant fried rice seasoning (BA3) has the potential to be developed as a practical, long-lasting, and widely favored Acehnese culinary product. This study employed a quantitative approach using an experimental method conducted at the Culinary Education Laboratory, Faculty of Teacher Training and Education (FKIP), Syiah Kuala University. The object of the study was fried rice with instant seasoning made from asam sunti. The subjects consisted of 4 expert panelists and 30 general consumer panelists. Data collection was carried out through organoleptic tests (color, aroma, texture, and taste) using a hedonic scale and consumer acceptance scale. The data were statistically analyzed using one-way ANOVA and LSD (Least Significant Difference) test at a 0.05 significance level with the assistance of SPSS software version 26.0. The results showed that the third treatment (BA3) produced fried rice with instant seasoning made from asam sunti that received the highest organoleptic scores in terms of color, aroma, texture, and taste. The BA3 recipe used a balanced composition of ingredients and spices, resulting in an appealing color, strong spiced aroma, dry texture, and savory taste favored by both expert panelists and consumers. Asam sunti instant fried rice seasoning (BA3) has the potential to be developed as a practical, long-lasting, and widely accepted Acehnese culinary product.